1988
DOI: 10.1243/pime_proc_1988_202_127_02
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Forces Produced by Waviness of the Rolling Surfaces of Thrust Loaded Ball Bearings Part 1: Theory

Abstract: Theoretical expressions are derived relating amplitude and wavelength of surface imperfections in thrust loaded ball bearings to vibration forces and frequencies produced under constant-speed operating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
110
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 4 publications
4
110
0
1
Order By: Relevance
“…The 435 former observation was also reported by Tiwari et al [105,106], and the latter by Tandon et al [46]. 436 Sopanen et al [54,55] ignored the slippage of the rolling elements (balls) [49] and neglected the centrifugal 437 forces acting on them, although it was shown that the modelled defect-related frequencies agree well with 438 the earlier results published in the literature [46,97,98,103,[105][106][107].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The 435 former observation was also reported by Tiwari et al [105,106], and the latter by Tandon et al [46]. 436 Sopanen et al [54,55] ignored the slippage of the rolling elements (balls) [49] and neglected the centrifugal 437 forces acting on them, although it was shown that the modelled defect-related frequencies agree well with 438 the earlier results published in the literature [46,97,98,103,[105][106][107].…”
supporting
confidence: 53%
“…While Sopanen et al [54,55] did not conduct any experimental work, they 429 compared their modelling results with those of similar studies available in the literature. For example, for 430 the localised raceway defects, the predicted results were compared with the results in reference [46], and for 431 the waviness, the modelling results were compared with the results reported in references [97,98,103,107].…”
mentioning
confidence: 99%
“…When the number of balls and waves are equal there would be severing vibrations. Wardle [9] showed that ball waviness produced vibrations in the axial and radial directions at different frequencies and also pointed out that only even orders of ball waviness produced vibrations.…”
Section: Article In Pressmentioning
confidence: 99%
“…When faults occur in the rolling element bearing, impulse-type vibration behavior appears [3]. There are many sources of vibration of bearings [4,5], some are inherent, such as the variable compliance effect, which cannot be guarded against but can be minimized with proper preloading and interference fitting; some are simply period repetitions, such as cage frequency. Others are due to unbalances in assembly and yet others are due to the waviness of rolling surfaces (no surface is perfectly smooth).…”
Section: Introductionmentioning
confidence: 99%